2003
DOI: 10.1148/radiol.2273020352
|View full text |Cite
|
Sign up to set email alerts
|

Air Trapping at CT: High Prevalence in Asymptomatic Subjects with Normal Pulmonary Function

Abstract: Various degrees of air trapping, including the mosaic or extensive types, can be observed in subjects with normal pulmonary function and have no correlation with the subject's current smoking status or cigarette consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 22 publications
4
60
2
5
Order By: Relevance
“…with minimal (<10%) air trapping, which may have yielded better within-subject repeatability. Several studies have reported similar ranges in air-trapping percentages in asymptomatic smokers, as high as 20%(6). We used FRC scans to measure air trapping rather than full expiratory scans because of subject difficulty in holding their breath at RV and because of know correlations, at FRC, between air-trapping and clinical metrics of lung disease(17, 18).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…with minimal (<10%) air trapping, which may have yielded better within-subject repeatability. Several studies have reported similar ranges in air-trapping percentages in asymptomatic smokers, as high as 20%(6). We used FRC scans to measure air trapping rather than full expiratory scans because of subject difficulty in holding their breath at RV and because of know correlations, at FRC, between air-trapping and clinical metrics of lung disease(17, 18).…”
Section: Discussionmentioning
confidence: 81%
“…Lung density measurements based upon the density histogram have been useful to quantify the presence and distribution of air trapping and emphysema-like lung regions in COPD and asthma patients, but the pattern and percentage can vary even among normal subjects(6). Subject differences in inspiratory and expiratory effort, scanner type, radiation dose, and reconstruction algorithms have considerable effect on quantification of regional parenchymal pathology and their association with global measures of lung function(710).…”
Section: Introductionmentioning
confidence: 99%
“…Although such ''gas trapping'' is apparent even in asymptomatic individuals who have normal lung function [86], it is markedly increased in patients with asthma and the degree of gas trapping is related to abnormalities of lung function [33,34,48,70,87].…”
Section: Gas Trappingmentioning
confidence: 99%
“…Regional air trapping was only scored as absent or present (three or more secondary lobules involved) while several studies have shown that some air trapping can also be seen in nonobstructive smokers, as in healthy volunteers [17][18][19]. This is also reflected in the high and similar prevalence rates of regional air trapping in nonobstructive smokers and healthy volunteers in their study.…”
mentioning
confidence: 83%